A Morphological Study of Placenta in Normal and Diabetic Pregnancies and Its Foetal Implications - Raj, Lisha S; Vasudevan, Sheela; ., Jayalekshmi (Annals of Pathology and Laboratory Medicine, 2019)
Background: The placenta is a foeto-maternal organ that separates the maternal and foetal circulations and plays a key metabolic role in pregnancy. Placental changes are directly proportional to the disease duration and its severity. In addition foetal outcome is also adversely influenced by pathological changes in placenta. . In the present study the focus is to bring out placental changes specifically associated with diabetes Methods: The placentae for the study were obtained from the in- patients of department of Obstetrics and Gynaecology, Sree Gokulam Medical College and Research Foundation, Venjaramoodu. 100 placentae were collected for the study. Among these 50 placentae were from mothers with uneventful antenatal period comprising the normal group and 50 placentae from mothers with GDM classified as GDM group. A descriptive study was done to assess the morphology of placentae in Gestational diabetes mellitus and to compare the same with that of normal pregnancies. The parameters included both gross and microscopy. Result: The morphometric parameters and gross observations like hematoma and calcification were increased in GDM. Microscopic findings like Syncytial knots, fibrinoid necrosis, Cytotrophoblastic proliferation, basement membrane thickening, obliterative endarteritis, Villous vascularity and villous stromal fibrosis (p<0.001) were significantly increased in GDM group. Significant percentage of placentae with more than 5% of immature villi was seen in GDM group. The birth weight of babies was increased in GDM group mothers compared to normal group Conclusion: Diabetes in pregnancy has a profound impact on both the placenta and the foetus. Both the villous and stromal parameters are altered by the high glycemic level.